Engineering nanostructured electrode materials for high performance sodium ion batteries: a case study of a 3D porous interconnected WS2/C nanocomposite. Issue 41 (16th September 2015) - Zhu, Changbao; Kopold, Peter; Li, Weihan; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract : A 3D porous interconnected WS2 /C nanocomposite is prepared by an ESD technique, which shows great potential for sodium anode materials. Abstract : Much attention is being paid to sodium ion batteries (SIBs) in view of the abundance of sodium sources and the cost issues. Layered transition metal dichalcogenides (such as MoS2 and WS2 ) have great potential to be used as anode materials for sodium storage owing to their high capacity. However, they still suffer from low rate capability and poor cycling stability. Compared to MoS2, WS2 has been scarcely studied in view of sodium storage. Here, we report, for the first time, a 3D porous interconnected WS2 /C nanocomposite prepared by an electrostatic spray deposition (ESD) technique, which is composed of nano-0D WS2, nano-1D CNTs and nano-2D reduced graphene oxide. Such a nanocomposite shows excellent rate performance and long cycling stability, demonstrating great potential for its use as a sodium anode. Moreover, this strategy can be applied to other electrode materials for both lithium and sodium batteries.